Single-chain polymer nanoparticles : synthesis, characterization, simulations, and applications - Pomposo, José A. (Weinheim, Germany : Wiley-VCH, 2017)
This first book on this important and emerging topic presents an overview of the very latest results obtained in single-chain polymer nanoparticles obtained by folding synthetic single polymer chains, painting a complete picture from synthesis via characterization to everyday applications. The initial chapters describe the synthetics methods as well as the molecular simulation of these nanoparticles, while subsequent chapters discuss the analytical techniques that are applied to characterize them, including size and structural characterization as well as scattering techniques. The final chapters are then devoted to the practical applications in nanomedicine, sensing, catalysis and several other uses, concluding with a look at the future for such nanoparticles. Essential reading for polymer and materials scientists, materials engineers, biochemists as well as environmental chemists
Synthetic Methods Toward Single-Chain Polymer Nanoparticles / Ozcan Altintas, Tobias S Fischer, Christopher Barner-Kowollik -- Computer Simulations of Single-Chain Nanoparticles / Angel J Moreno, Federica Lo Verso -- Characterization of Single-Chain Polymer Nanoparticles: Analytical Techniques / Ashley M Hanlon, Kyle J Rodriguez, Ruiwen Chen, Elizabeth Bright, Erik B Berda -- Structure and Dynamics of Systems Based on Single-Chain Polymer Nano-Particles Investigated by Scattering Techniques / Arantxa Arbe, Juan Colmenero -- Dynamically Folded Single-Chain Polymeric Nanoparticles / Yiliu Liu, Anja RA Palmans -- Metal Containing Single-Chain Nanoparticles / Inbal Berkovich, Victoria Kobernik, Stefano Guidone, Norberto Gabriel Lemcoff -- Colloidal Unimolecular Polymer Particles: CUP / Michael R Van De Mark, Ashish Zore, Peng Geng, Fei Zheng -- Single-Chain Nanoparticles via Self-Folding Amphiphilic Copolymers in Water / Takaya Terashima, Mitsuo Sawamoto -- Applications of Single-Chain Polymer Nanoparticles / Jon Rubio-Cervilla, Edurne González, José A Pomposo
Keywords: Polymers; Nanoparticles